Avtobiografija in kočljivost zvrstnih opredelitev - Juvan, Marko (Slavistična revija, 2009)
On the example of Cankar's MOje življenje (My life( (1914/1920) and its intertextual connection to Rousseau's Confessions, the article discusses the contradiction between the singularity and the generic nature of the verbal expression of "life" in autobiography. In this rspect, the autobiography again proves to be a genre that questions genology and genological systems.
Keywords: avtobiografije; Cankar, Ivan, 1914-1920; Cankar, Ivan: Moje življenje; genologija; literarna teorija; literarni žanri; literary theory; singularnost; Slovene literature; slovenska književnost